The Original "Free Trade": Exchange of Botanical Products and Associated Plant Knowledge in Northwestern North America - Turner, Nancy J.; Loewen, Dawn C. (Anthropologica, 2022)
Long-standing and far-reaching trade networks for culturally important plants are documented for British Columbia and neighbouring areas from archaeological, historical and ethnographic records, as well as recollections of contemporary Aboriginal people. Plant resources and products manufactured from plants comprised a substantial portion of traditional and contemporary traded goods. Examples include: dried edible seaweed, commonly traded from coastal communities inland; dried soapberries, saskatoon berries and other berries; hazelnuts; cedar-root and cedar-bark baskets; basket materials; and Indian-hemp fibre and twine. In addition to the plant materials, knowledge associated with these resources was exchanged, and trade has had cultural and ecological implications extending well beyond simple subsistence.